Rekayasa Pemijahan Ikan Betok (Anabas Testudineus Bloch) Menggunakan Ekstrak Hipofisa Ayam Broiler - Ghofur, Muarofah; Sugihartono, Muhammad; Arifin, M Yusuf; Wijaya, Andre (Jurnal Akuakultur Sungai dan Danau, 2024)
Betok fish is an economically important fish and is very popular with the community but not many people have cultivated this Betok fish. For this reason, there needs to be an innovation in aquaculture technology so that Betok fish production increases. Stimulation of the work of pituitary hormones of broiler chickens to stimulate gonad maturation in Betok fish spawning to increase production due to overfishing. The purpose of this study was to test the effectiveness of broiler chicken pituitary extract on spawning betok fish (A. testudineus, Bloch) on latent time of ovulation, fecundity, and hatching rate. The study time for 30 days used 4 treatments 3 times, with P0 treatment: Control, P1 treatment: Broiler Chicken Pituitary Extract 0.2 ml/kg, P2 treatment: Broiler Chicken Pituitary Extract 0.4 ml/kg, and P3 treatment: Broiler Chicken Pituitary Extract 0.6 ml/kg. The results showed that treatment A. 0.2 ml / kg had a good effect on the ovulation latency time of betok fish, which was 8 hours 7 minutes, fecundity of 6618 eggs and hatchability of 94.67%. The results of water quality measurements showed that the temperature ranged from 28o-29o C, dissolved oxygen of 3.2-4.8 mg / L, pH of 7.3-7.7 and ammonia of 0.012-0.013 mg / L.